Cancer prevalence and its determinants in Hungary: Analyzing data from the 2009, 2014, and 2019 European Health Interview Surveys. - Amr Sayed Ghanem; Eszter Vargáné Faludi; Róbert Bata; Emese Mezei; Vanessza Hadar; Marianna Móré; Ágnes Tóth; Attila Csaba Nagy (PLoS ONE)
Background and aim Hungary has the fifth highest cancer incidence rate in the European Union, with an age-standardized rate (ASR) of 336.7 per 100,000 according to GLOBOCAN 2022. Additionally, Hungary holds the highest cancer mortality rate in the EU, with an ASR of 148.1 per 100,000. This study aimed to investigate the sociodemographic, lifestyle, and chronic disease-related factors affecting cancer prevalence in the Hungarian population. Materials and methods Data from the 2009, 2014, and 2019 installments of the European Health Interview Survey conducted in Hungary were pooled, resulting in a representative sample of 16,480 individuals. Weighted multiple logistic regression models were used to analyze the data, with goodness of fit assessed using the Hosmer-Lemeshow test. The best-fitting models were further evaluated using ROC analysis to calculate the Area Under the Curve (AUC) to assess discriminative ability. Results Urban residency was associated with higher cancer odds in 2014 (OR 1.85 [CI: 1.08-3.16]) and the pooled data (OR 1.44 [CI: 1.08-1.9]). Employed individuals had lower odds of cancer (2014: OR 0.34 [CI: 0.16-0.74]; pooled: OR 0.64 [CI: 0.45-0.92]). Among comorbid conditions, peptic ulcer (2009: OR 1.74 [CI: 1.13-2.69]; 2019: OR 3.2 [CI: 1.58-6.47]; pooled: OR 1.83 [CI: 1.31-2.54]) and chronic liver disease (2009: OR 3.52 [CI: 1.73-7.17]; pooled: OR 2.5 [CI: 1.4-4.47]) were significantly associated with higher cancer odds. Reporting bad health was linked to increased cancer risk (2009: OR 2.92 [CI: 1.87-4.58]; 2014: OR 5.52 [CI: 3.23-9.45]; 2019: OR 2.23 [CI: 1.26-3.95]). Conclusion Comorbid conditions such as peptic ulcer and chronic liver disease significantly increase cancer risk in Hungary. Urban residents require targeted preventive measures, and unemployment should be addressed. Early detection through appropriate screening and effective management of comorbid conditions are essential to prevent escalation and reduce overall cancer prevalence.